PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, KOMITE AUDIT, KOMISARIS INDEPENDEN, DAN AUDIT DELAY TERHADAP INTEGRITAS LAPORAN KEUANGAN : PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Felita, Thea; Budiadnyani, Ni Putu; Laksmi P, Kadek Wulandari; Dewi, Putu Pande R. Aprilyani (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This research aims to examine the influence of company size, institutional ownership, audit committee, independent commissioner, and audit delay on the integrity of financial reports (in manufacturing companies listed on the Indonesia Stock Exchange in 2021-2023). The research approach used is quantitative by applying multiple linear regression analysis using SPSS software to process data. The sample was selected using a purposive sampling method, with a total sample of 348 over a three year period. The results of the research state that company size has a negative and insignificant effect on the integrity of financial reports, while independent commissioners and audit committees have a negative and significant effect on the integrity of financial reports, independent commissioners have a positive and significant effect on the integrity of financial reports, and audit delay has a positive and insignificant effect. to financial reports